Evil empire : a reckoning with power - Chasman, Deborah; Cohen, Joshua (Forum (Cambridge, Mass.), 2018)
"“All history,” writes Maximillian Alvarez in his contribution to this issue, “is the history of empire—a bid for control of that greatest expanse of territory, the past.” Evil Empire confronts these histories head-on, exploring the motivations, consequences, and surprising resiliency of empire and its narratives. Contributors grapple with the economic, technological, racial, and rhetorical elements of U.S. power and show how the effects are far-reaching and, in many ways, self-defeating. Drawing on a range of disciplines—from political science to science fiction—our authors approach the theme with imagination and urgency, animated by the desire to strengthen the fight for a better future.." -- Provided by distributor.